MARKET ORIENTATION OF RICE FARMERS IN ACEH BESAR REGENCY - Litna Nurjannah Ginting; Zulkarnain Zulkarnain; Dian Retno Intan; Noratun Juliaviani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Market orientation is a crucial factor in the success of farmers in the increasingly competitive era of modern agriculture. This study aims to measure the level of market orientation among rice farmers in Aceh Besar Regency using the Crop Specific Marketability Index (CMI) and Market Orientation Index (MOI). Data analysis shows that the market orientation level of rice farmers in Aceh Besar Regency is still in the moderate category. The obtained CMI value of 0.62 indicates that rice farmers in Aceh Besar sell 62% of their rice production. The MOI shows a varied distribution with values ranging from 0 to 0.9. The average MOI value among rice farmers in Aceh Besar is 0.5, meaning that farmers allocate only 50% of their land to produce crops for the market. This indicates that most rice farmers in the study area produce for sale and to meet household consumption needs. Based on these findings, it is recommended that farmers' awareness and capacity to adopt market-oriented agricultural practices through extension services be increased, thereby enhancing productivity and the competitiveness of agricultural products.